Empirical review on the accounting measurement of the Covid-19 pandemic: impact on the business industries / Siti Aisyah Omar, Farhana Hasbolah and Abul Bashar Bhuiyan - Omar, Siti Aisyah; Hasbolah, Farhana; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The Covid-19 global pandemic has affected most companies financially as it has led to massive uncertainties across all sectors and industries. In such a situation, it is required to refine the accounting information. The accounting index can intuitively and vividly reveal the economic operation situation and provide ‘wind vane’, ‘monitor’, and ‘early warning device’ for economic decision making. The study used available online empirical recourses by the name of Covid-19 pandemic Impact on the Industries and Accounting measurement of the business industries in different online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald full text, Scopus, and EBSCO HOST, etc. The review findings show that there are different accounting indexes used in the period before and after the Covid-19 outbreak. The majority of indexes were based on big data portrait analysis and measures the impact of the Covid-19 on various industries. The findings of the study also identified that the basic industry was less affected while the rest of the industries were significantly affected by the epidemic. Moreover, in terms of the cost calculation, there are various industries that have increased at different levels especially, aviation, tourism, and other service industries have been greatly impacted. The findings of the study will be used to draw policy guidelines for the industries which were significantly affected by the epidemic.